The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1007/bf02552713
|View full text |Cite
|
Sign up to set email alerts
|

Substrate preferences for lipase‐mediated acyl‐exchange reactions with butteroil are concentration‐dependent

Abstract: Substrate preferences for pancreatic lipase~mediated acylexchange reactions with butteroil were concentrationdependent for the series of acyl donors and alcohol acceptors evaluated. For acidolysis reactions, the initial reao tion rates and percent reaction yields after 18 h at 50 pmol acyl donor per gram substrate mixture were similar for nfatty acids and their methyl and glycerol esters. At 400-500 pmol g-1 (and greater), order of initial reaction rates and percent reaction yield was fatty acid glycerol ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 21 publications
5
18
1
Order By: Relevance
“…Therefore, it seems that an excess of caprylic acid above a molar ratio of approximately 6, diminishes the reaction rate. This observation concurs with the data of Kuo and Parkin, 24 and is explained by the acidification of the enzyme layer caused by an excess of the free fatty acids. 24 However, since the hydrolysis of triglycerides to diglycerides should precede the exchange of fatty acid, this decrease may also be provoked by the decrease of intermediate diglycerides that give rise to an increase in the free fatty acid concentration.…”
Section: Kineticssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, it seems that an excess of caprylic acid above a molar ratio of approximately 6, diminishes the reaction rate. This observation concurs with the data of Kuo and Parkin, 24 and is explained by the acidification of the enzyme layer caused by an excess of the free fatty acids. 24 However, since the hydrolysis of triglycerides to diglycerides should precede the exchange of fatty acid, this decrease may also be provoked by the decrease of intermediate diglycerides that give rise to an increase in the free fatty acid concentration.…”
Section: Kineticssupporting
confidence: 91%
“…This observation concurs with the data of Kuo and Parkin, 24 and is explained by the acidification of the enzyme layer caused by an excess of the free fatty acids. 24 However, since the hydrolysis of triglycerides to diglycerides should precede the exchange of fatty acid, this decrease may also be provoked by the decrease of intermediate diglycerides that give rise to an increase in the free fatty acid concentration. This result is consistent with the results of Akoh and Huang, 11 who, working with the same system, found that the maximum proportion of dicapryl, oleilglycerol (C37 in their nomenclature) was obtained with a molar ratio range of 4-6.…”
Section: Kineticssupporting
confidence: 91%
“…This could also be true with the increase of caproic and butyric acid in our reaction medium. This increase was attributed to acidification of the microaqueous environment of the lipase (16).…”
Section: Resultsmentioning
confidence: 97%
“…This result is consistent with the findings of (Yankah and Akoh 2005), and Paez et al (2003). Excess free fatty acids in the medium acidify the enzyme layer because of high levels of free or ionized carboxylic acid groups or cause desorption of water from the interface which causes a decrease in the activity of the enzyme (Kuo and Parkin, 1993). In addition, high substrate ratios are economically unfeasible, because purification of the products would require a cost-increasing extra separation step.…”
Section: Resultsmentioning
confidence: 99%